2020
DOI: 10.1016/j.ejogrb.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in Covid-19 pregnant women: Preeclampsia or severe infection?

Abstract: We report the case of a severe COVID-19 infection in which the diagnosis of preeclampsia (PE) was wrongly assumed because of proteinuria. This case raises both the question of the predictive value of proteinuria and the differential diagnosis between preeclampsia and the severe form of COVID-19 in pregnant women. Despite numerous publications related to the pandemic, data remain limited regarding COVID-19 infections in pregnant women. The reported rates of severe infections range between 14 % (severe pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
(1 reference statement)
0
6
0
3
Order By: Relevance
“…In other words, it may be difficult to clinically distinguish this syndrome from “true” preeclampsia because they both share characteristics of the severe endothelial dysfunction seen in nonpregnant patients. 7 , 30 …”
Section: Commentmentioning
confidence: 99%
“…In other words, it may be difficult to clinically distinguish this syndrome from “true” preeclampsia because they both share characteristics of the severe endothelial dysfunction seen in nonpregnant patients. 7 , 30 …”
Section: Commentmentioning
confidence: 99%
“…Despite the clinical manifestation in COVID-19 pregnant women seems to remain the same as in non-pregnant patients, several studies suggest that pregnant women infected with COVID-19 may be at risk for preterm delivery (294)(295)(296). Recent papers also reported cases of pre-eclampsia and manifested gestational hypertension in COVID-19 pregnant women (297)(298)(299). An analysis of the WAPM study on COVID-19 reported that early gestational age at infection, maternal ventilatory supports and low birthweight are the main determinants of adverse perinatal outcomes in fetuses with maternal COVID-19 infection (300).…”
Section: Male and Female Reproductive System And Pregnancymentioning
confidence: 99%
“…Herzerkrankungen und COVID-19 haben ebenfalls gemeinsame Symptome, die in der Schwangerschaft zu einer Fehldiagnose führen können [354]. Geburtshilfliche Differentialdiagnosen sollten in jeder Abklärung einer vermuteten COVID-19-Erkrankung berücksichtigt werden [355]. Es wurde über eine Koinzidenz von PRES [356] und COVID-19-Krankheit berichtet, sodass die Differentialdiagnostik eines PRES besonders wichtig ist [357].…”
Section: Vertikale Transmissionunclassified